Boundary rings and N=2 coset models - Lerche, Wolfgang; Walcher, Johannes (Nuclear physics. B, Particle physics, 2002)
We investigate boundary states of N=2 coset models based on Grassmannians Gr(n,n+k), and find that the underlying intersection geometry is given by the fusion ring of U(n). This is isomorphic to the quantum cohomology ring of Gr(n,n+k+1), which in turn can be encoded in a “boundary” superpotential whose critical points correspond to the boundary states. In this way the intersection properties can be represented in terms of a soliton graph that forms a generalized, Zn+k+1 symmetric McKay quiver. We investigate the spectrum of bound states and find that the rational boundary CFT produces only a small subset of the possible quiver representations.